Identification of bilateral asymmetries in lower limbs of soccer players by vertical jumps on a double force platform - Menzel, H. J.; Chagas, M. H.; Cruz, G. L. H. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The purpose of this study was to identify bilateral dynamic asymmetries of the lower limbs of forty six Brazilian professional soccer players by countermovement jumps on a double force platform. Maximal ground reaction force, impulse and maximal power output were registered and bilateral asymmetries identified if the bilateral difference was greater than 15%. A two factor structure of bilateral differences was found represented by maximal force and impulse production/maximal power output. Impulse production and maximal power output are more reliable indicators for bilateral asymmetries than maximal ground reaction force. In order to analyze dynamic bilateral asymmetries more completely, it seems to be necessary to apply a combination of different test procedures which consist of vertical jumps, isokinetic tests and maximal isometric contractions.